2018
DOI: 10.3390/medsci6040087
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Development of Transglutaminase 2 Inhibitors as Pharmaceutical Lead Compounds

Abstract: Transglutaminase 2 (EC 2.3.2.13; TG2 or TGase 2) plays important roles in the pathogenesis of many diseases, including cancers, neurodegeneration, and inflammatory disorders. Under normal conditions, however, mice lacking TGase 2 exhibit no obvious abnormal phenotype. TGase 2 expression is induced by chemical, physical, and viral stresses through tissue-protective signaling pathways. After stress dissipates, expression is normalized by feedback mechanisms. Dysregulation of TGase 2 expression under pathologic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Although these inhibitors were reported to induce a conformational change of TGase 2 that affects GTP binding to TGase 2, the binding of these inhibitors to TGase 2 did not apparently block p53 binding to TGase 2. This result corroborates previous reports regarding p53 binding to TGase 2, in that it is specifically the N-terminus of p53 that interacted with the N-terminus of TGase 2 [21][22][23]64]. This suggests indirectly that streptonigrin induced p53 activation by competing with p53 for binding to TGase 2 [23].…”
Section: Anti-cancer Effect Of Tgase 2 Inhibition In Ccrccsupporting
confidence: 91%
See 3 more Smart Citations
“…Although these inhibitors were reported to induce a conformational change of TGase 2 that affects GTP binding to TGase 2, the binding of these inhibitors to TGase 2 did not apparently block p53 binding to TGase 2. This result corroborates previous reports regarding p53 binding to TGase 2, in that it is specifically the N-terminus of p53 that interacted with the N-terminus of TGase 2 [21][22][23]64]. This suggests indirectly that streptonigrin induced p53 activation by competing with p53 for binding to TGase 2 [23].…”
Section: Anti-cancer Effect Of Tgase 2 Inhibition In Ccrccsupporting
confidence: 91%
“…This is only possible in ccRCC because over 90% of p53 in ccRCC is wild type. Thus, collectively these observations represent a breakthrough for the clinical field because they identify TGase 2 as a specific therapeutic target for ccRCC, and the marked potential for binding inhibitors between TGase 2 and p53 such as GK921 [71] and streptonigrin [23] to become the first therapeutics for ccRCC (reviewed in [64]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports proposed TG2 inhibition as a useful tool for therapeutic approaches. For example, it has been reported that the GK921 TG2 inhibitor, overlapping with the p53-binding site of TG2, was able to induce apoptosis in renal cell carcinoma [37]. Similarly, the inhibition of TG2 by the microRNA (miR)-214 was associated with a relevant suppression of viability, invasion and migration of colorectal carcinoma cells [36].…”
Section: Resultsmentioning
confidence: 99%